ASEAN Mutual Recognition Agreement (MRA) Arrangement and Implementation of MRA for the Dancer Profession in Supporting Labor Mobility in the ASEAN Region - Markus, Jessica Tania; Pribadi, Sandi Januar (Jurnal Indonesia Sosial Sains, 2025)
This research explores the implementation and impact of ASEAN Mutual Recognition Agreements (MRAs) in the context of the ASEAN Framework Agreement on Services (AFAS), focusing on the mobility of professional workers in the ASEAN region. This study proposes the implementation of MRA in the creative professions sector, especially the profession of dancers, which has not received adequate attention within the MRA framework. This study aims to analyze the effectiveness of the implementation of MRA in the engineering sector and identify the potential for adopting a similar model in the performing arts sector. Using a juridical normative approach, this study conducts a qualitative analysis with a comparative approach, comparing the application of MRAs in the engineering sector and creative professions. The results show that although MRAs have succeeded in increasing the mobility of professional workers in the engineering sector, their application to creative professions faces major challenges, such as the disharmony of qualification standards and non-uniform accreditation systems. This study suggests the need to develop a more inclusive legal framework and harmonize qualification standards to support the implementation of MRAs in the creative sector. The implication of this study is the strengthening of ASEAN economic and cultural integration through broader recognition of creative professions, which can enrich the region's cultural identity and enhance the competitiveness of the ASEAN creative economy globally.